PENGARUH PENERAPAN METODE HYPNOTEACHING TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MAN 1 BANDA ACEH - Rajulul Azka (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the effect of implementing the hypnoteaching method on students’ learning motivation in Islamic Religious Education (IRE) classes at MAN 1 Banda Aceh. The background of this study stems from the low level of students’ learning motivation in IRE classes, as evidenced by a lack of participation, attention, and active engagement in the learning process. The research method employed a quantitative approach with an ex post facto design. Data were collected through a questionnaire distributed to 60 eleventh-grade students and analyzed using simple regression to determine the magnitude of the relationship between the independent variable (hypnoteaching) and the dependent variable (student learning motivation). The results indicate that the hypnoteaching method has a positive and significant effect on student learning motivation. The coefficient of determination (R²) value of 0.518 indicates that 51.8% of the variation in students’ learning motivation is influenced by the application of hypnoteaching, while the remainder is influenced by other factors outside the scope of this study. These findings confirm that positive suggestion techniques, empathetic communication, and emotional reinforcement in hypnoteaching can enhance students’ interest, attention, and spiritual engagement in Islamic Education (PAI) learning. This study concludes that hypnoteaching is an effective and relevant pedagogical approach for enhancing students’ learning motivation in religious education. Further research is recommended to employ a mixed-methods approach and expand the scope of the study to yield a more comprehensive understanding of the effectiveness of hypnoteaching across various educational contexts.